Social media narratives and media prosumer - Karbaum Padilla, Gerardo (2018)
Storytelling is a human action. Humankind practices it from memorial times until these days. Stories are important for species survival since through these knowledge is transfer from generation to the next one and social identity of communities is built. Each era is defined by social and cultural changes as well as technological innovations. At the same time, these three concepts weighs in the creation of stories, as set out today: stories are produced and widespread on social media as communicational actions, which are linked by a new teller: the media prosumer